Profile of evolocumab and its potential in the treatment of hyperlipidemia - Cicero AF; Colletti A; Borghi C (Dove Medical Press, 2015)
Arrigo FG Cicero, Alessandro Colletti, Claudio Borghi Medical and Surgical Sciences Department, University of Bologna, Bologna, Italy Abstract: Despite the proven efficacy of statins, they often fail to achieve low-density lipoprotein (LDL) cholesterol goals, especially in high-risk patients. Moreover, a large number of subjects cannot tolerate statins or full doses of these drugs, in particular patients with familial hypercholesterolemia. Thus, there is a need for additional effective LDL cholesterol-reducing agents. Evolocumab (AMG145) is a monoclonal antibody inhibiting proprotein convertase subtilisin/kexin type 9 that binds to the liver LDL receptor and prevents it from normal recycling by targeting it for degradation. Phase I, II, and III trials revealed that, on subcutaneous injection, either alone or in combination with statins, evolocumab is able to reduce high LDL cholesterol levels from 54% to 80%, apolipoprotein B100 from 31% to 61%, and lipoprotein(a) from 12% to 36%, in a dose-dependent manner. The incidence of side effects seems to be low and mainly limited to nasopharyngitis, injection site pain, arthralgia, and back pain. Evolocumab is an innovative powerful lipid-lowering drug, additive to statins and/or ezetimibe, with a large therapeutic range associated with a low rate of mild adverse events. If the available data are confirmed in long-term trials with strong outcome measures, evolocumab will become an essential tool in the treatment of a large number of high-risk patients, such as those affected by familial hypercholesterolemia, those who are unable to tolerate an efficacious statin dosage, and those at very high cardiovascular risk and unable to achieve their target LDL cholesterol levels with currently available lipid-lowering therapies. Keywords: hypercholesterolemia, lipid-lowering drugs, proprotein convertase subtilisin/kexin type 9, AMG145